PEMBUATAN BIOETANOL DARI MAHKOTA BUAH NANAS VARIETAS CAYANE DENGAN MENGGUNAKAN SACCHAROMYCES CEREVISIAE - Metta Wijayanti (PT. Jurnal Center Indonesia Publisher, 2024)
The scarcity of petroleum resources or other fuel sources encourages efforts to find alternative energy, namely Bioethanol. Alternative raw materials that can be utilised in the manufacture of bioethanol from biomass are pineapple crowns. Making Bioethanol from Pineapple Fruit Crown Cayane Variety by Using Saccharomyces cerevisiae Microbes is by varying the weight of yeast and the optimum fermentation time on the level of bioethanol produced. In this study using NaOH 1.5%w to degrade the lignin content in the crown of pineapple varieties cayane and H2SO4 2%v to convert cellulose into glucose. The research used variations in yeast weight of 7.5%; 10%; 12.5%w and variations in fermentation time of 2; 3; 4; 5 days in the fermentation process. While the purification process uses simple distillation with operating conditions 78oC-80oC for 2.5 -4 hours. Bioethanol obtained was tested for refractive index and gask romatography (GC). The test results obtained the optimum weight of yeast is 12.5 grams at 3 days fermentation time with bioethanol content of 6.154%.